AWARENESS OF USING RINGER LACTAT SOLUTION IN DENGUE VIRUS INFECTION CASES COULD INDUCE SEVERITY - Soegijanto, Soegeng; Sari, Desiana W.; Yamanaka, Atsushi; Kotaki, Tomohiro; Kameoka, Masanori; Konishi, Eiji (Indonesian Journal of Tropical and Infectious Disease, 2013)
Background: In 2012, serotype of Dengue Virus had changed from Den-2 and Den-3 to Den-1. In 5â10 years ago, serotype of Den-1 case showed a mild clinical manifestation; but now as a primary case it can also show severe clinical manifestation. One of indicator is an increasing liver enzyme, AST and ALT, with level more than 100â200 U/L. Aim: To getting a better solutions for this problem. Method: Obsevasional Study had been done in medical faculty of Airlangga University (Dr. Soetomo and Soerya hospital) Surabaya on MeiâAugust 2012. There were 10 cases of dengue virus infection were studied, 5 cases got Ringer Acetate solution (Group A) and 5 cases got Ringer Lactate solution (Group B). The diagnosis was based on criteria WHO 2009. Result: Five cases of Dengue Virus Infection had showed a liver damage soon after using Ringer Lactate solution; AST and ALT were increasing more than 100â200 U/L; but the other 5 cases showed better condition. It might be due to use Ringer Acetate that did not have effect for inducing liver damage. By managing carefully, all of the cases had shown full recovery and healthy condition when being discharged. Conclusion: Using Ringer Acetate as fluid therapy in Dengue Virus Infection is better to prevent liver damage than using Ringer Lactate.